Microwave-assisted in-situ catalytic upgrading of heavy oil - Anbari, Hossein (2023)
This work concerns reservoir simulation of heavy oil recovery and experimental studies of downhole oil catalytic upgrading enhanced with microwaves. Numerical simulations are a key tool to investigate the Toe to Heel Air Injection (THAI) operating mechanism due to the limitations in experimental (3D combustion cell) THAI investigations. In this study, the THAI process was numerically studied through reservoir simulations. The starting point of the numerical simulation study was to develop a new experimental scale THAI model. The new experimental scale THAI model was history-matched against previous 3D combustion tube experiments. The experimental scale THAI model was then scaled up to a field scale model. The field scale THAI models were then used to study two types of THAI well arrangements, namely the direct line drive (DLD) and staggered line drive (SLD). The DLD and SLD well arrangements were compared in terms of sweep efficiency, water cut, and oxygen utilisation. Although, the DLD well arrangement resulted in earlier oil production, it was shown that, in terms of overall performance, the SLD well arrangement is superior to the DLD well arrangement.